Localized English in Indonesian Social Media: Implications for English Language Learning - Miftahush Shalihah (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study examines the emergence of localized English expressions in Indonesian social media discourse, highlighting how English is adapted and reinterpreted in multilingual digital contexts. While previous studies on English in Indonesia have primarily focused on formal domains such as education and language policy, limited attention has been given to informal online communication where linguistic innovation is highly visible. This study aims to analyze how English lexical items are re-semanticized and creatively transformed by Indonesian users on social media platforms. The study employed a qualitative approach using data collected from Instagram posts and comments, focusing on selected examples of English-derived expressions such as boba, gas, voucher, server, and suamiable. The analysis compares the conventional meanings of these terms in Inner Circle English with their localized meanings in Indonesian usage. The findings reveal that English functions as a flexible linguistic resource, undergoing processes of semantic shift, metaphorical extension, and lexical blending. These localized forms reflect users’ creativity as well as their ability to adapt global linguistic resources to local cultural contexts. The study concludes that English in Indonesian social media is not merely borrowed but actively reconstructed, contributing to the dynamic development of English in the Expanding Circle.